Lipid Profile, Apparent Digestibility and Protein Efficiency Ratio of Sprague Dawley Rats Fed With Red Palm Fat Diets - Wan Rosli, W. I.; Babji, A.S.; Aminah, A. (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2007)
Processed meat products, such as burgers, sausages, meatballs, salami and nuggets are currently popular with urban consumers. However, in general, they are high in cholesterol, total lipid and saturated fatty acids. Four beef burger formulations were prepared, each containing 15% fat from either beef fat (control), palm fat (PF), red PF or a blend of PF and red PF at a ratio of 1:1 at 15% fat. A rat assay was carried out to determine lipid profile, apparent digestibility (AD) and protein efficiency ratio (PER) of rats fed with beef burger diets containing palm based fats. Treatment with PF and red PF beef burger diets did not affect the total cholesterol concentration but resulted in higher HDL-cholesterol concentration in their blood serum. The rats fed with dried burger diets containing PF and red PF had higher AD value (90.0% and 89.3%, respectively) and was not significantly different (P < 0.05) compared to the group fed with dried burger containing beef fat (90.7) over the 10 days experimental diet period. PER values of all treatments except for casein were not significantly different (P < 0.05). There was also no difference (P < 0.05) in food intake and body weight gain between all rats fed with dried burger containing different types of palm based fats. In summary, the utilization of PF and red PF in beef burger increased the HDLcholesterol and had no effect on the concentration of total cholesterol in rat blood serum. Addition of palm based fats into beef burgers did not change AD and PER.